When the present lies in the past: [Present under Past] in subjunctive clauses in Uruguayan Spanish - Brenda Laca; Eduardo Correa Soares; Leticia López; Saveria Colonna (Glossa, 2022)
On the basis of corpus and experimental evidence, this paper claims that the ongoing process of change affecting the use and interpretation of the [Present under Past] pattern in subjunctive argument clauses in some Spanish varieties is sensitive to the syntactic/semantic type of the clause. The pattern deviates from Sequence-of-Tense grammar in not giving rise to double access effects. In the variety explored in this paper, this only happens in the argument clauses of causative, directive, and volitional predicates, i.e. in a type of clause which is held to be lower in a scale of clausehood than the argument clauses of predicates of belief and assertion.@font-face{font-family:Calibri;panose-1:2 15 5 2 2 2 4 3 2 4;mso-font-charset:0;mso-generic-font-family:auto;mso-font-pitch:variable;mso-font-signature:3 0 0 0 1 0;}p.MsoNormal, li.MsoNormal, div.MsoNormal{mso-style-parent:"";margin:0cm;margin-bottom:.0001pt;mso-pagination:widow-orphan;font-size:12.0pt;font-family:Calibri;mso-fareast-font-family:Calibri;mso-bidi-font-family:Calibri;}div.Section1{page:Section1;}